2009
DOI: 10.1038/nature08503
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cortical microcircuits by unitary GABA-mediated volume transmission

Abstract: Gamma-aminobutyric acid (GABA) is predominantly released by local interneurons in the cerebral cortex to particular subcellular domains of the target cells1,2. This suggests that compartmentalized, synapse specific action of GABA is required in cortical networks for phasic inhibition2–4. However, GABA released at the synaptic cleft diffuses to receptors outside the postsynaptic density and thus tonically activates extrasynaptic GABAA and GABAB receptors, which include subtypes of both receptor families especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
373
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 354 publications
(429 citation statements)
references
References 29 publications
45
373
0
11
Order By: Relevance
“…Ultrastructural analyses of climbing fiber terminals and molecular layer interneurons have shown tight membrane appositions external to but in the region of active zones (Kollo et al, 2006), which provides an indirect morphological support for glutamate spillover transmission at these particular junctions. In addition, a recent report showed that cortical neurogliaform interneurons do not require direct synaptic junctions to induce unitary GABAmediated responses in target neurons (Olah et al, 2009), corroborating our evidence that pure spillover connections may constitute a precise phasic mode of communication between interneurons and NG2 cells in the mature brain.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Ultrastructural analyses of climbing fiber terminals and molecular layer interneurons have shown tight membrane appositions external to but in the region of active zones (Kollo et al, 2006), which provides an indirect morphological support for glutamate spillover transmission at these particular junctions. In addition, a recent report showed that cortical neurogliaform interneurons do not require direct synaptic junctions to induce unitary GABAmediated responses in target neurons (Olah et al, 2009), corroborating our evidence that pure spillover connections may constitute a precise phasic mode of communication between interneurons and NG2 cells in the mature brain.…”
Section: Discussionsupporting
confidence: 75%
“…Recently, an unusual mechanism of pure spillover transmission that induce phasic responses in the absence of classical synaptic activity has been described for neuronal connections in the cerebellum (Szapiro and Barbour, 2007) and the neocortex (Olah et al, 2009). By using pharmacological agents, we tested whether this mode of neuronal communication also controls GABAergic transmission from interneurons to NG2 cells in the barrel cortex after the second PN week.…”
Section: A Switch From Synaptic To Extrasynaptic Transmission Betweenmentioning
confidence: 99%
“…It should also be emphasized that perisomatic interneurones establish several thousand terminals at a density of approx. 80 per 100 μm 3 (Oláh et al, 2009), a value that is much higher than what reported for principal cells (cf. for CA3 pyramidal cells Wittner and Miles, 2007).…”
Section: Interneurons As Gaba Releasing Nerve Cellsmentioning
confidence: 62%
“…Another type of basket cells, containing CCK, also form perisomatic contacts onto pyramidal cells; however, they are distinguished from the PV þ variety by their slower, accommodating firing patterns (Hefft and Jonas, 2005) that integrate neuromodulatory information with faster network activity (Freund, 2003;Varga et al, 2009). Interconnected networks of NPY þ neurogliaform cells mediate regional tonic inhibition through extrasynaptic volume transmission in multiple cortical and subcortical regions (Manko et al, 2012;Olah et al, 2009;Price et al, 2005). Martinotti cells, containing CR, CB, SST, NPY, and/or CCK, span both cortical lamina and cortical columns and synapse onto pyramidal cell tuft dendrites in layer I (Markram et al, 2004).…”
Section: Development Of the Gabaergic Systemmentioning
confidence: 99%